1998
DOI: 10.7589/0090-3558-34.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Northern Bobwhites as Disease Indicators for the Endangered Attwater's Prairie Chicken

Abstract: Because of limited access to the endangered Attwater's prairie chicken (Tympanuchus cupido attwateri), we used a related species, the northern bobwhite (Colinus virginianus), as a surrogate for disease evaluation. Free-living northern bobwhites (n = 62) on the Attwater Prairie Chicken National Wildlife Refuge (near Eagle Lake, Texas, USA) were examined during spring and fall 1993 for helminthic endoparasites and specific antibodies against the infectious agents responsible for nine infectious diseases. Trichos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…The surrogate species approach has been promoted in health studies of endangered taxa to provide otherwise unattainable data for use in assessing potential exposures and disease burden to guide species recovery plans. For example, in order to better understand threats to the endangered Attwater's prairie chicken, sympatric northern bobwhite were assessed for helminthic endoparasites and specific antibodies against infectious agent (Purvis et al 1998), and a similar parasite community was revealed when compared with direct studies of the prairie chickens conducted earlier (Peterson et al 1998). We suggest that the sandhill crane is a candidate surrogate species for the whooping crane because it is the closest North American relative to the whooping crane, it is abundant, and the Mid-continent population of sandhill cranes has an overlapping range with whooping cranes.…”
Section: Introductionmentioning
confidence: 99%
“…The surrogate species approach has been promoted in health studies of endangered taxa to provide otherwise unattainable data for use in assessing potential exposures and disease burden to guide species recovery plans. For example, in order to better understand threats to the endangered Attwater's prairie chicken, sympatric northern bobwhite were assessed for helminthic endoparasites and specific antibodies against infectious agent (Purvis et al 1998), and a similar parasite community was revealed when compared with direct studies of the prairie chickens conducted earlier (Peterson et al 1998). We suggest that the sandhill crane is a candidate surrogate species for the whooping crane because it is the closest North American relative to the whooping crane, it is abundant, and the Mid-continent population of sandhill cranes has an overlapping range with whooping cranes.…”
Section: Introductionmentioning
confidence: 99%
“…These four birds came from two of three remaining APC populations. Purvis et al (1998) also observed specific antibodies to P. multocida in 3 of 53 (5.7%) northern bobwhites (Colinus virginianus) collected from the APCNWR. Periodic outbreaks of avian cholera have occurred in wintering waterfowl in coastal Texas .…”
Section: Survival and Mortality Factorsmentioning
confidence: 71%
“…T. tenuis has been experimentally shown to affect red grouse body condition, productivity, and survival . Purvis et al (1998) found T. cramae in 97% of northern bobwhites collected from APCNWR. Peterson et al (1998), Purvis et al (1998), andPeterson (2004) all stressed the importance of determining whether T. cramae limits or regulates APC populations.…”
Section: Survival and Mortality Factorsmentioning
confidence: 87%
See 1 more Smart Citation
“…Multiple ecology, management, and conservation issues have been addressed using Northern Bobwhite as a model (Scott, 1985). Purvis et al (1998) suggested Northern Bobwhites as an indicator or sentinel species for the endangered Attwater's Prairie-Chicken (Tympanuchus cupido attwateri). Quail were trapped under TPWD permit SPR-1005-1521, and handling and sampling of animals were in accordance with and consistent with standards approved and set forth by the Institutional Animal Care and Use Committee, Texas Tech University field protocol 10017-05.…”
mentioning
confidence: 99%